Sonchus oleraceus L. Promotes Gastroprotection in Rodents via Antioxidant, Anti-Inflammatory, and Antisecretory Activities - Vecchia, Cristian A. D.; Locateli, Gelvani; Serpa, Patricia Z.; Bianchin Gomes, Denise; Ernetti, Jackeline; Miorando, Daniela; Zanatta, Maria Eduarda D. C.; Kaio Silva Nunes, Ruan; Wildner, Silvana M.; Gutiérrez, Max V. [UNESP]; Vilegas, Wagner [UNESP]; Somensi, Lincon B.; et al. (Hindawi, 2022)
Sonchus oleraceus L. is an edible and medicinal plant used to treat stomachache and gastric ailments around the world. Thus, this study aimed to determine the gastroprotective mode of action of hydroalcoholic extract of S. oleraceus (HES). Mice were treated with HES before induction of gastric ulceration by ethanol/HCl. The area and histological appearance of ulcers were quantified, and mucus was measured histochemically. The effects of HES on inflammatory and oxidative markers were assessed in the ulcerated tissue. In addition, we investigated the gastric acid antisecretory activity of HES in pylorus-ligated rats. Chemical analyses of HES and its antioxidant activity were also performed in vitro. The HES (30 or 300 mg/kg) reduced the ulceration by 71.5 and 76.2%, respectively, compared with vehicle (p<0.001), and the histological analysis confirmed the macroscopic results with elevation in mucin levels by 361.4 and 477.5%, respectively, compared with vehicle (p<0.001). Moreover, the gastroprotection was accompanied by increases in GSH levels and in SOD, CAT, and GST activities; in parallel to a reduction in MPO activity and TNF levels. Furthermore, HES reduced the total acidity, and pepsin activity of the gastric juice of rats by 61 and 63%, respectively, compared to the vehicle. Phytochemical analysis indicated that luteolin-7-O-β-D-glucoside is the main active compound annotated in HES. Was also found that HES scavenged the DPPH radical with an IC50 of 15.41 μg/mL. In conclusion, the gastroprotective effects of HES involve reductions in oxidative stress and inflammatory injury, in conjunction with an increase in mucus layer and inhibition of gastric secretion. This study advances in elucidating the modes of the antiulcer potential of S. oleraceus and contributes to the prospection of new gastroprotective molecules.